Editorial - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
This JIFAM 6 (Special Issue 1) January 2024 publishes 5 papers related to slope stability and soil improvement methods to develop the sustainable asset management for national road infrastructures. As regulated in Indonesian Scientific Journal Accreditation, a Scientific Journal can publish the Supplement and Special Edition. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for the sixth volume (Special Issue 1).